Evaluation of a Novel Method of Fuze Programming Based on the Number of Projectile Own Revolutions - Wojciech FURMANEK; Józef GACEK; Grzegorz JĄCZEK (Problemy Mechatroniki)
This paper presents an innovative method of programming fuses for airburst munitions based on the principle of counting the number of revolutions a projectile makes around its centre line along the flight trajectory in order to determine the distance travelled by the projectile. The proposed innovative method of fuse programming was compared to other known methods of fuse programming based on the results of a computer simulation of firing a 40 mm grenade launcher under near-real conditions. For this purpose, a methodology was developed for external ballistic calculations using a mathematical model of the three-dimensional motion of a non-deformable flying object considered to be a rigid body with six degrees of freedom in an ISO 1151 coordinate system. Simulations were carried out taking into account actual firing conditions for 40 mm grenade launcher ammunition armed with fuses programmed by each of the methods evaluated. Targets located at various distances were fired upon and the level of scatter of actual fuse ignition points relative to the expected fuse ignition point was evaluated for each programming method. It was concluded that the method of determining the distance travelled by the projectile with the principle of counting the projectile’s revolutions under real conditions resulted in a scatter of the fuse ignition points greater than with the time delay-based methods. In conclusion it was observed that the method of determination for the revolving projectile based on counting the projectile’s rotations along the flight trajectory did not guarantee the required precision of the fuse ignition point locations. This means that the application of the methods to determine the distance of projectile burst along the flight trajectory did not increase the effectiveness of airburst fragmentation munitions.